The Influence of Social Media and Motivation on Generation Z Interest in Becoming a Teacher with Teaching Experience as an Intervening Variable - Damayanti, Salsabila Wanda Putri; Wulandari, Ruri Nurul Aeni (MANAZHIM, 2025)
The teaching profession is central to the development of human resources and the advancement of national progress. However, a declining interest among Generation Z in pursuing teaching careers raises concerns about the future availability of qualified educators. This study investigates the influence of social media and motivation on students’ interest in becoming teachers, with teaching experience serving as a mediating variable. Employing a quantitative methodology and an explanatory research design, the study surveyed 166 students from the 2021 and 2022 cohorts of the Office Administration Education Program at Surabaya State University. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings reveal that social media does not have a significant direct effect on students’ interest in becoming teachers, while motivation shows a positive and significant influence. Individuals with higher motivation are more likely to express interest in a teaching career. Both social media and motivation significantly influence teaching experience, which in turn strongly affects interest in the teaching profession. Furthermore, the study confirms that social media and motivation indirectly influence career interest through teaching experience, highlighting the critical role of hands-on teaching practice in shaping students’ aspirations toward educational careers.